Green power, materials and manufacturing technology and applications : selected, peer reviewed papers from the International Conference on Green Power, Materials and Manufacturing Technology and Applications (GPMMTA2011), July 15-18, 2011, Chongqing, China - Yang, Aimin; Qu, Jingguo; Qu, Xilong (TTP, Trans Tech Publications, 2011)
The aim of this special volume was to facilitate the exchange of information on the best practices for Sustainable Power, Sustainable Materials, Green Manufacturing Technology and Applications, etc. It provides an opportunity for engineers and scientists, in academia, industry and government, to address the most innovative research and development ideas, including technical challenges, social and economic issues, and to discuss ideas, results, work-in-progress and experience concerning all aspects of Green Power, Materials and Manufacturing Technology and Applications. The work offers the read.
Keywords: Sustainable engineering -- Congresses.; Sustainable development -- Congresses.; Green products -- Congresses.; elektronické knihy; electronic books